Students' perceptions of Photomindset media in English language teaching - Ghaisani, Fadhilah; Manurung, Sulastri; Siahaan, Safnidar (Journal of English Language Teaching and Learning (JETLE), 2025)
The demand for innovative and attractive teaching resources in the digital age is crucial for enhancing students' language proficiency and learning engagement. This study examines students' perceptions of Photomindset as media in English teaching and learning. This study employed a mixed-method approach, combining a close-ended questionnaire and interviews. The study involved 32 students in one of Junior High School in Batam, Indonesia and utilized the Technology Acceptance Model (TAM) to assess their perceptions. Three students with the highest TAM scores were selected for interviews to gain deeper insights into their perception. Data were analyzed using descriptive statistics to describe the tendency of students' perceptions of Photomindset and the relationship between perceived usefulness and perceived ease, as measured by Pearson correlation. Thematic analysis was employed to identify recurring themes and pattern from interviews. The results showed that students have positive perception of Photomindset with the mean score of 116 for Perceived Usefulness and 115 for Perceived Ease of Use. However, there is no correlation between perceived usefulness and perceived ease of use. The findings suggests that Photomindset is an effective, beneficial and user-friendly tool for enhancing English learning.